Effects of deforestation on the properties of soil of Sal forests in Bangladesh - Hossain, Mohammad Zabed; Saha, Mihir Lal; Aziz, Chaman Binta; Hoque, Sirajul (Dhaka University Journal of Biological Sciences, 2011)
This study examined the effect of deforestation on the soil properties (physico-chemical and bacterial) of the Sal (Shorea robusta Roxb. Ex Gaertn.) forests in Bangladesh. Physico-chemical properties and the bacterial colony counts of soil were studied by comparing a natural Sal forest site with deforested and planted with Menjium site, deforested and planted with Mahogoni site, as well as deforested but not planted but covered with profuse growth of Axonopus compressus grass species site. Moisture content was significantly lower in the deforested and planted with Menjium site and deforested and planted with Mahogoni site than the natural forest site and the deforested but not planted site. Total organic carbon, total nitrogen and available nitrogen contents were significantly lower in the natural forest site. Significantly higher number of bacterial colony and higher organic carbon and moisture contents were found in the deforested but not planted site indicating that both organic carbon and moisture content were important for microbial growth. The present study clearly showed that deforestation significantly altered the soil physico-chemical and bacterial communities of the Sal forests. It was also revealed that plantation with different exotic plants were found to be different in influencing soil properties. Key words: Bacterial colony; Deforestation effects; Sal forest; Soil physico-chemical properties DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8945 DUJBS 2010; 19(1): 63-72